In any way I can - Tylee, Cree (University of Waterloo, 2025)
In any way I can explores memory, longing, and impermanence through photographic and sculptural installations. This body of works embody the paradox of presence and absence within the realms of experience, death, and loss. Key themes include an investigation of the precarity of identity and familial histories, emphasizing how the static, photographic and fugitive image can deteriorate, fade, and transform over time. Within the installation, the concept of home is presented and serves as both physical and metaphysical framework, to process memory and self-formation. Using the gallery as a nonlinear spatial diary, I reimagine personal and collective histories through materialized recollections of objects and places, some of which predate my existence. In this diaristic space, photographs—both personal and discarded—interact with organic, second-hand, and inherited materials, mapping an emotional geography that questions the fallibility of memory. In any way I can acknowledges the fluid boundaries between tangible environments and the internal landscapes they become, reflecting the universal experience of becoming and unbecoming.
Keywords: photography; sculpture; memory; emotional geography; alternative process photography